Global catastrophic risk and security implications of quantum computers. - Majot, Andy; Yampolskiy, Roman (Futures, 2015)
With advancements in quantum computing happening almost weekly it is time to examine the effects this new technology will have on society and current computational systems. Specifically, cryptographic systems need to be carefully analyzed since the introduction of quantum computational resources would render discrete logarithm and factoring based cryptographic systems like those based on Rivest, Shamir, Adleman (RSA) and Elliptic Curve Cryptography (ECC) algorithms woefully obsolete. These algorithms are widely used in the form of digital certificates, message encryption, and even physical authentication devices like Radio Frequency Identification (RFID) badges. With this technology compromised by quantum computing, governments and other organizations would be able to eavesdrop on private citizens with relative ease. This has the potential to cause a slew of rights violations and atrocities leading to catastrophe. With compromised digital certificates 3rd parties could masquerade as trusted organizations. This would call many types of digital transactions like into question, including those related to stock exchanges, personal banking, and software verification. By eroding this previously solid foundation of trust global scale economic catastrophes are not out of the question. This paper introduces quantum computing to the study of catastrophic threats since the use of quantum technology while existing vulnerable encryption schemes are still in place raises severe safety issues. These issues are addressed here along with a proposed two-fold solution involving the development and maturation of post-quantum cryptographic algorithms coupled with government and international regulation. This regulation would promote the containment and responsible use of quantum computers in order to help alleviate some of the security issues posed by outdated cryptographic systems in a post-quantum environment.